Smart Village Sebagai Jawaban Desa Masa Depan - Bahirah, Hilda Indah (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
This paper aims to examine the concept of Smart Villages which is trying to be applied to the village of the future. Village conditions in Indonesia from year to year always experience a decline in terms of welfare and also the economy, this is due to uncontrolled urbanization resulting in village conditions getting worse. In the era towards society 5.0, problems related to this village can be overcome by implementing smart village solutions in Indonesian villages. Smart villages are believed to be able to improve village welfare conditions. The research methods used are library research. The results of this study explain that many villages in Indonesia are not ready to implement this smart village. Due to several factors such as poverty, low literacy, lack of attention to their own area and also problems. There needs to be special attention in the implementation of this smart village, presented in several stages. smart village includes various methods to optimize its implementation, it is necessary to prepare villages and communities to become eco-villages before entering the smart village concept. This study recommends the local village government as well as the community to pay more attention to the smart village concept, because smart villages cannot be generalized to the smart city concept, even though it is a derivative. This can be an initial capital in understanding the smart village concept.